Exploring the Efficacy of Basketball Shooting: A Comprehensive Analysis of Success Rates (International Journal of Innovative Research in Computer Science & Technology, 2023)
The present study evaluated success  rate of basketball shooting for different skill levels. A  total of 10 subjects (5 skilled and 5 unskilled) participated  in this study. The main goal of the study was to provide  the preliminary data for further studies in finding  mechanisms of improving shooting success rate during  basketball games. This larger constraint is thought to  require performers to change their motion control strategy  to maintain accuracy and create a tremendous urge to  push the ball the moment it is released. Still, many players  have difficulty adapting to longer distance shooting. The  results suggested that there were main effects of group  and distance, but, no interaction effect was found. In  conclusion, shooting success rate were affected by  distance regardless of skill levels in basketball shooting.
Keywords: Basketball Shooting; Release Time; Field Goal